Relationships between dopamine D2/3 receptor availability and social-environmental factors in humans. (6th February 2022) - Calakos, Katina C.; Rusowicz, Aleksandra; Pittman, Brian; Gallezot, Jean-Dominique; Potenza, Marc N.; Cosgrove, Kelly P.; Matuskey, David
Graphical abstract: Highlights: Social factors influence the human brain and psychiatric outcomes. Dopamine D2/3 receptor availability was imaged with positron emission tomography. Population size and education level of participants' neighborhoods were collected. Living in a populous, less educated area is linked with higher D2/3 receptor availability. This extends the study of neural correlates of social status to population factors. Abstract: Social factors are associated with psychiatric outcomes and brain function. Relationships between local population data obtained from Social Explorer analyses of the American Community Survey (2014–2018) and dopamine D2/3 receptor (D2/3 R) availability were explored in this retrospective analysis of [ 11 C]PHNO positron emission tomography (PET) imaging data ( n = 70). Larger local population size and lower percentage of the population with a bachelor's degree or higher were significantly associated with higher striatal D2/3 R availability, suggesting that living in a populous area with fewer educational resources may be accompanied by stressors with concomitant dopaminergic changes. Future prospective, collaborative studies are needed to better understand the precise etiology of the observed relationships.